Evaluation Report on Provision of House Sites Cum-House Construction Assistance to the Rural Landless Labour Households - Planning Commission (Planning Commission, 1987)
At the instance of the Housing Division of the Planning Commission, Programme Evaluation Organisation undertook an evaluation study of the scheme for provision of House-sites-cum Construction assistance to the rural landless labourers, The objective of the scheme was to provide house sites, free of cost, to the landless agricultural labourers/artisans, so as to enable them to build house/hut thereon with their own resources and' to live without eviction threats by the owners of the land. The objectives of the evaluation study as decided by the Technical Advisory Commit tee (TAC ) were (i) To study the methods followed for identification of the rural landless labour households for the allotment of house Sites-cum-house construction assistance under the scheme
Programme Evaluation Organisation Planning Commission Government of India